Analysis of bus priority scheme in Singapore - Zhang, Yedi. (2013)
The objective of the study is to give comprehensive analysis of bus priority schemes implemented in Singapore. Literature review was conducted to provide background knowledge of various bus priority schemes. Evaluation for effectiveness of Bus Lane Scheme in Singapore was the focus of study. Three road scenarios with different schemes were chosen for evaluation. Site experiments were conducted to collect traffic data of roads and vehicles.